Discovery of substrate cycles in large scale metabolic networks using hierarchical modularity. - Sridharan, Gautham Vivek.; Ullah, Ehsan.; Hassoun, Soha.; Lee, Kyongbum. (2016)
Background: A substrate cycle is a set of metabolic reactions, arranged in a loop, which does not result in net consumption or production of the metabolites. The cycle operates by transforming a cofactor, e.g. oxidizing a reducing equivalent. Substrate cycles have been found experimentally in many parts of metabolism; however, their physiological roles remain unclear. As genome-scale metabolic models become increasingly available, there is now the opportunity to comprehensively catalogue substrate cycles, and gain additional insight into this potentially important motif of metabolic networks.; Keywords: Substrate cycles, Modularity, Metabolic networks.; Springer Open.